MANAJEMEN PELAYANAN PUBLIK BERBASIS TEKNOLOGI MELALUI E-PBB DI KECAMATAN GUNUNGPATI KOTA SEMARANG - Prajatama, Kevin Satria; Larasati, Endang; Lituhayu, Dyah (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro)
Public services in Indonesia continue to strive to realize the concept of good governance, one of which is by implementing the digitization of the PBB program in electronic form (e-PBB). The Gunungpati District Government of Semarang City is one of the government agencies that intensifies this program to make it easier for its people to pay PBB, given that Gunungpati District is the sub-district with the lowest PBB income in 2019 in Semarang City. The purpose of this research is to describe and analyze how the implementation of tax payments using e-PBB, and to find out strategies that make it easier for people to make tax payments via e-PBB in Gunungpati District, so that there is no tax arrears. The study used a qualitative descriptive approach with primary and secondary data types obtained by literature review, observation, and field studies. The object of the research consisted of 2 government sources and 1 community resource, with the research location being Gunungpati District, Semarang City. The analytical method used is descriptive analytical. The results showed that the implementation of e-PBB in Gunungpati District used a management pattern of Organizing, Actuating, and Controlling. In addition, Gunungpati District has implemented several programs to provide convenience to the community in paying PBB-P2 and to pursue the target for PBB-P2 payments. This effort has partially fulfilled the application of the New Public Service paradigm.